2005
DOI: 10.1186/1471-5945-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Acne and smoking: is there a relationship?

Abstract: Background: There are contradictory reports on the relationship between acne vulgaris and cigarette smoking. The objective of this study was to examine the relation between acne and cigarette smoking in a case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 11 publications
2
41
2
5
Order By: Relevance
“…In the present study, as in that by Rigopoulos et al, 18 parents were the most popular source of information about acne. 28,29 There is little evidence on the role of alcohol in the pathogenesis of acne, although Suh et al 30 found an associa-tion between alcohol consumption and acne exacerbation. Our results reflect the important roles of family members, friends, and the mass media in not only informing and advising schoolchildren but also in correcting their misconceptions of acne.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, as in that by Rigopoulos et al, 18 parents were the most popular source of information about acne. 28,29 There is little evidence on the role of alcohol in the pathogenesis of acne, although Suh et al 30 found an associa-tion between alcohol consumption and acne exacerbation. Our results reflect the important roles of family members, friends, and the mass media in not only informing and advising schoolchildren but also in correcting their misconceptions of acne.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore information on possible confounders was lacking On the other hand, Jemec et al [ 110 ] found that smoking was not signifi cantly associated with acne in a random sample of 186 subjects. Similarly, Firooz et al [ 111 ] compared smoking status of 293 acne patients to 301 patients suffering from other dermatological conditions in a case-control study. After accounting for acne's higher prevalence and greater severity in men, no signifi cant correlation was found between acme and smoking.…”
Section: Acne and Smokingmentioning
confidence: 97%
“…Four major factors are involved in the pathogenesis including increased sebum production, hypercornification of the pilosebaceous duct, an abnormality of the microbial flora especially colonization of the duct with Propionibacterium acnes ), and the production of inflammation 3. It seems that several factors influence acne including diet, menstruation, sweating, stress, ultra violet radiation and occupation 4. Positive association between intake of milk and acne was reported and this findings support earlier studies and suggests that the metabolic effects of milk are sufficient to elicit biological responses in consumers 5.…”
Section: Introductionmentioning
confidence: 99%